Genre-based text analysis :undergraduates' writing of information reports - Irene, Ngu Tien Tien (Universiti Malaysia Sarawak, UNIMAS, 2009)
This study aims to analyse the undergraduates’ writing of information reports. The ability of tertiary undergraduates to acquire academic writing skills in fulfilment of assignment requirement is a great concern among lecturers and undergraduates. Production of quality academic writings requires understanding of the communicative functions of those writings. A case study was conducted to find out whether UNIMAS undergraduates, majoring in different disciplines over the university, were able to produce quality academic writings – information report, which comprise of appropriate use of schematic structures and language features as required by the assignment questions after undergoing an intensive writing training in an English generic course, English for Academic Reading and Writing (ARW). Selection of the sample texts was done where 100 written assignments of information report genre were collected from all undergraduates who attended ARW in the 1st semester of Year 2008/2009. Genre analysis based on the theoretical framework of an information report developed by Derewianka (1992) was used for analysis and evaluation of the undergraduates’ written works. The findings showed that some undergraduates were not competent in writing a good and correct information report. They were weak in differentiating information report genre from the other genres. Even though the writings produced were discovered to have the basic structures that seemed to look like an information report, they mixed the formal features of information report with the formal features of explanation, discussion and descriptive genres. However, it was discovered that the targeted undergraduates who were able to write in correct generic structure were competent in utilising the language features of information report genre although there were some minor grammatical errors in terms of choice of tenses used such as past and present tenses as well as the singular and plural forms of present tense. The research findings contribute to the syllabus design and development of academic writing courses to tackle the undergraduates’ specific needs and emphasise on the importance of genre analysis in revealing aspects of efficient academic writing skills.